What `s luck got to do with it? Superstitious behaviors in sports - Welch, R. B. (Track Coach, 2015)
Leo Manzano, one of America`s premier distance runners, sometimes performs a convoluted ritual just before the gun goes off. In it, he licks his index finger and then uses it to touch, in order, his forehead, inside of each elbow, Adam`s apple, chest, knees, and ankles, and finally crosses himself. You can see this for yourself on YouTube (https://www.youtube.com/watch?v=sAgBIGFDfo). What compels him to do this? It seems apparent that he is trying to bring himself good luck and/or ward off bad luck. In short, he is engaging in superstitious behavior, the subject of this paper. What follows is a review of the current knowledge about superstitious behaviors, with a special emphasis on those in sports. Fortunately, there is no reason to believe that sports superstitions differ in any significant way from those found elsewhere. Topics that will be addressed include: • The definition and major categoriesof superstitious behavior • The kinds of people most likely to be superstitious • The athletic skills and sports for which superstitions are especially common • How and why athletes acquire superstitious behaviors • Under what circumstances they are most likely to put them to use • Why superstitious behaviors are so difficult to give up • Do superstitions work? (The answer may surprise you!). And finally, • Take-away messages for track & field coaches and their athletes